Synthesis of A-seco derivatives of betulinic acid with cytotoxic activity - Urban, Milan; Sarek, Jan; Klinot, Jiri; Korinkova, Gabriela; Hajduch, Marian (Journal of natural products, 2004)
In this study, the relationships between the chemical structure and cytotoxic activity of betulinic acid (1) derivatives were investigated. Eight lupane derivatives (1-8), one of them new (6), five diosphenols (9-13), four of them new (10-13), two new norderivatives (14 and 15), five seco derivatives (16-20), four of them new (16, 17, 19, and 20), and three new seco-anhydrides (21-23) were synthesized from 1, and their activities were compared with the activities of known compounds. The effects of substitution on the A-ring and esterification of the carboxyl group in position 28 on cytotoxicity were of special interest. Significant cytotoxic activity against the T-lymphoblastic leukemia cell line CEM was found in diosphenols 9 and 13 (TCS(50) 4 and 5 micromol/L) and seco-anhydrides 22 and 23 (TCS(50) 7 and 6 micromol/L). All compounds were also tested on cancer cell lines HT 29, K562, K562 Tax, and PC-3, and these confirmed activity of diosphenols 9, 10, and 11 and anhydride 22. Diosphenols, as the most promising group of derivatives, were further tested on four more lines (A 549, DU 145, MCF 7, SK-Mel2).
Keywords: Pentacyclic Triterpenes; kyselina betulinová; Inhibitory Concentration 50; screeningové testy protinádorových léčiv; fytogenní protinádorové látky; Molecular Structure; Structure-Activity Relationship; lidé; inhibiční koncentrace 50; Betulinic Acid; techniky kombinatorické chemie; nádorové buňky kultivované; pentacyklické triterpeny; Antineoplastic Agents, Phytogenic; molekulární struktura; triterpeny; Nuclear Magnetic Resonance, Biomolecular; Tumor Cells, Cultured; nukleární magnetická rezonance biomolekulární; vztahy mezi strukturou a aktivitou; Drug Screening Assays, Antitumor; Triterpenes; Combinatorial Chemistry Techniques; Humans